Using nonlinear jumps to estimate cubic stiffness nonlinearity: An experimental study - Tang, Bin; Brennan, Michael John; Vicente, Lopes Jr; Samuel, da Silva; Ramlan, Roszaidi (Institution of Mechanical Engineers, 2016)
Attempts are being made to improve mechanical design by using nonlinearity rather than eliminating it, especially in the area of vibration control and in energy harvesting. In such systems, there is a need to both predict the dynamic behavior and to estimate the system properties from measurements. This paper concerns an experimental investigation of a simple identification method, which is specific to systems in which the behavior is known to be similar to that of a Duffing-type system. It involves the measurement of jump-down frequencies and the amplitudes of displacement at these frequencies. The theoretical basis for the method is briefly described as, is an experimental investigation on a beamshaker system. The results are comparable with those determined by the restoring force surface method. The method described in this article has the advantage that the data can be collected and processed more easily than the restoring force surface method and can be potentially more suitable for the engineering community than existing identification measures.